von Bertalanffy growth model with autocorrelated errors - Venugopalan, R; ., Prajneshu (Indian Journal of Fisheries, 2011)
Three procedures namely, linearised version of the von Bertalanffy growth(VBG) model, nonlinear estimation of the VBG model with independently andidentically distributed (i.i.d) error term, and nonlinear estimation of the VBGmodel with autocorrelated errors were applied to the age-length data of Indianmackerel under the assumptions of monophasic as well as diphasic growth.Based on sound statistical techniques, it is demonstrated that nonlinearestimation procedure with autocorrelated error structure performs the best.